Crime Films and Lexical Change: Can an Analysis of an Electronic Corpus of Fifteen Crime Films Help Students Understand Semantic Mutations? - Jean-Louis Vidalenc (Sillages Critiques)
Lexical change proves one of the most puzzling aspects of the evolution of English for non native speakers. While some mechanisms which explain shifts in the semantic programs of known lexical items are well documented others like a puritan background have been rarely discussed. In this paper, we will suggest that Noir films provide evidence of the lexical creativity caused by this puritan strain and may explain why so many English words have to be translated by French words they are not associated with in most dictionaries. We suggest that a better understanding of the forces at work in language evolution will not only help students of English as a second language but may provide some insight into more theoretical approaches.